2015
DOI: 10.1371/journal.pone.0118919
|View full text |Cite
|
Sign up to set email alerts
|

Loss from Treatment for Drug Resistant Tuberculosis: Risk Factors and Patient Outcomes in a Community-Based Program in Khayelitsha, South Africa

Abstract: BackgroundA community based drug resistant tuberculosis (DR-TB) program has been incrementally implemented in Khayelitsha, a high HIV and TB burden community in South Africa. We investigated loss from treatment (LFT), and post treatment outcomes of DR-TB patients in this setting.MethodologyLFT, defined as interruption of treatment for ≥2 consecutive months was assessed among patients initiating DR-TB treatment for the first time between January 2009 and July 2011. Patients were traced through routine data sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 23 publications
(30 reference statements)
0
37
0
6
Order By: Relevance
“…In South Africa, transmission of MDR/RR-TB caused around 64% of MDR/RR -TB cases diagnosed at re-treatment, which is supported by molecular epidemiology studies indicating substantial clonal spread of multiple MDR-TB strains [11]. In addition to a strong emphasis on improved treatment adherence, consideration should be given to additional efforts that may reduce TB transmission within disease “hot spots” [31, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, transmission of MDR/RR-TB caused around 64% of MDR/RR -TB cases diagnosed at re-treatment, which is supported by molecular epidemiology studies indicating substantial clonal spread of multiple MDR-TB strains [11]. In addition to a strong emphasis on improved treatment adherence, consideration should be given to additional efforts that may reduce TB transmission within disease “hot spots” [31, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…483 Counselling and treatment literacy delivered by trained and paid lay health counsellors or drug-resistant tuberculosis survivors are crucial. 484 Such counselling should be individualised and include ongoing assessments of barriers to adherence and strategies for addressing them, because an individual's ability to adhere can change over time depending on his or her life circumstances.…”
Section: The Lancet Respiratory Medicine Commissionmentioning
confidence: 99%
“…A study in the Western Cape province of South Africa using cohort data from four South African treatment sites, 483 identified criteria for treatment failure, including duration of uninterrupted treatment for 12 months, three consecutive positive sputa, and a declining clinical condition. Decisions on treatment discontinuation should always be made by a multidisciplinary team, including the individual being treated and his or her support network.…”
Section: Patient-centred Approach To Treatment Discontinuation and Pamentioning
confidence: 99%
“…They defined LTFU as "A TB patient who did not start treatment or whose treatment was interrupted for 2 consecutive months or more." Since then, several papers have started reporting according to this new term and definition [3][4][5][6][7][8][9][10].…”
Section: Definitionmentioning
confidence: 99%
“…Among the various sociodemographic characteristics, age is a recognized factor associated with LTFU. Studies from India, Brazil, and China revealed that elderly patients have higher LTFU [4,[68][69][70], whereas studies from Norway, Botswana, and South Africa suggested that adolescents have significant risk [8,30,71]. One study from the UK even suggested a wider range of age of 15-44 years as a high-risk group for LTFU [11].…”
Section: Individual Factorsmentioning
confidence: 99%